Treatment of cytomegalovirus retinitis in AIDS patients with intravitreal ganciclovir - Somsanguan Ausayakhun (2018)
Background: Cytomegalovirus (CMV) retinitis is the most common opportunistic ocular infection in AIDS patients, and frequently leads to blindness if untreated. Intravitreal ganciclovir proved to be effective in stopping the progression of the disease. Objectives: To determine the efficacy and complications of intravitreal ganciclovir (2 mg in 0.1 ml per injection) to control CMV retinitis. Study design: A retrospective non-randomized interventional case series. Material and Method: The participants were 363 consecutive patients with CMV retinitis treated at the CMV Retinitis Clinic, Maharaj Nakorn Chiang Mai Hospital over the period from June 2001 to December 2003.The affected eyes received weekly intravitreal injections of 2 mg of ganciclovir until the lesions were inactive, then 2-4 weeks each time continuously or until relapse. If the lesions relapsed, then the weekly schedule was re-started. Results: In 568 treated eyes at the time of last follow up, visual acuity remained stable in 343 (60%), improved in 76(13%), and decreased in 149 (26%). Of these, 33 retinal detachments, 6 intravitreal hemorrhages, 6 endophthalmitis, and 2 cataract occurred. Bilateral disease occurred in 22% of patients who first came with unilateral involvement. Conclusion: Intravitreal ganciclovir appeared to be a worthwhile therapeutic alternative for CMV retinitis patients with unaffordable or intolerant to systemic anti-CMV therapy, but the complications of intravitreal injections should also be recognized.